Genetic and virulence factors behind the success of high-risk Pseudomonas aeruginosa clones: insights from comparative genomics and an experimental infection model - de Sales, Romário Oliveira; Leaden, Laura; Martins, Dayblegschwel Santos; Koga, Paula; Toniolo, Alexandra do Rosario; Gatti de Menezes, Fernando; Mori, Marcelo Alves; Martino, Marines D. V.; Severino, Patricia (Frontiers in Microbiology, 2025)
IntroductionPseudomonas aeruginosa causes severe healthcare-associated infections. High-risk clones are defined by global dissemination and multidrug resistance, yet virulence is heterogeneous. We sought to map accessory-genome determinants associated with high-risk clones by integrating whole-genome sequencing (WGS) with a Caenorhabditis elegans infection model.MethodsWe analyzed 84 clinical isolates plus publicly available genomes using WGS, phylogenomics, and resistome/virulome profiling. Virulence was measured by C. elegans slow-killing (SK). A GWAS of accessory-genome subelements (AGEs) identified loci with high- (HVA) or low-virulence association (LVA). Coding sequences were annotated with Prokka and InterPro.ResultsAlthough high-risk and sporadic clones carried a similar total number of antimicrobial-resistance genes, 15/67 (22.38%) genes/variants were enriched in high-risk clones, producing class-level enrichment (p < 0.002) for aminoglycosides, phenicols, trimethoprim, sulfonamides, and tetracyclines, but not β-lactams or fosfomycin. Many resistance determinants are recognized mobile-element cargo such as integron cassettes or plasmid/ICE-borne genes (e.g., aadA, dfrB, blaVIM-2, crpP, cmlA, floR), indicating a mobility-linked resistome in high-risk clones. GWAS identified 113 AGEs linked to SK virulence (42 HVA, 71 LVA). HVA regions were enriched for pyoverdine (fpvA, pvdE, pvdD) and LPS O-antigen (wbpA/B/D) loci, whereas LVA regions were enriched for ICE/conjugation/integrase motifs. cdsA and clpP were newly associated with P. aeruginosa virulence. Phenotypically, high-risk clones were more often strong biofilm producers and none were non-producers. High-risk clones were not consistently more virulent in SK, suggesting success reflects persistence traits (mobile DNA and biofilm under antibiotic pressure).ConclusionAccessory-genome GWAS revealed two risk dimensions: acute-virulence programs (HVA) versus mobility functions (LVA) favoring persistence and spread. Because SK measures acute virulence, readouts did not align with high-risk designations. Genomic reports should combine high-risk assignment with accessory-genome and effector profiling to support earlier containment and mechanism-aware, biofilm-focused care.